John Russell Young papers - Young, John Russell, 1840-1899.; Young, Mary Dow Davids
Correspondence, diaries, writings including an annotated biography, Dow family papers, scrapbook, photographs, and other papers relating chiefly to Young's career as a journalist and to his association with Ulysses S. Grant. Includes correspondence and diaries of Young's wife, Mary Dow Davids Young. Subjects include national politics; a world tour, 1877-1879, made by Ulysses S. Grant accompanied by Young; and an 1896 visit of Li Hongzhang to the United States. Includes letters written by Dwight D. Eisenhower to Dorothy Mills (Young) during his years at the United States Military Academy.
Correspondents include Edward Porter Alexander; Chester Alan Arthur; Henry Ward Beecher; James Bryce, viscount Bryce; Salmon P. Chase; Samuel Langhorne Clemens; Roscoe Conkling; Jay Cooke; Augustin Daly; Charles A. Dana; Charles Dickens; Ralph Waldo Emerson; John W. Forney; James A. Garfield; Henry George; James B. Gordon; Ulysses S. Grant; Horace Greeley; Benjamin Harrison; John Hay; Oliver Wendell Holmes; O.O. Howard; William Dean Howells; Osmun Latrobe; Charles Appleton Longfellow; James Russell Lowell; Anson G. McCook; William McKinley; Mrs. Stephen Crosby Mills; Edwin D. Morgan; Wendell Phillips; Whitelaw Reid; Carl Schurz; Philip Henry Sheridan; William T. Sherman; Daniel Edgar Sickles; Hoke Smith; Henry M. Stanley; Charles Sumner; Bayard Taylor; Henry Watterson; Andrew Dickson White, and G.R. Young.
Microfilm edition of diaries, 1865-1898, available
Microfilm produced from originals in the Manuscript Division.
Journalist, editor, diplomat, and Librarian of Congress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection related to the Library of Congress Archives.
Keywords: Alexander, Edward Porter, -- 1835-1910 -- Correspondence; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Bryce, James Bryce, -- Viscount, -- 1838-1922 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Clemens, Samuel Langhorne, -- 1835-1910 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Cooke, Jay, -- 1821-1905 -- Correspondence; Daly, Augustin, -- 1838-1899 -- Correspondence; Dana, Charles A. -- 1819-1897 -- Correspondence; Dickens, Charles, -- 1812-1870 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Emerson, Ralph Waldo, -- 1803-1882 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; George, Henry, -- 1839-1897 -- Correspondence; Gordon, James B. -- 1822-1864 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Holmes, Oliver Wendell, -- 1809-1894 -- Correspondence; Howard, O. O. -- 1830-1909 -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Latrobe, Osmun -- Correspondence; Li, Hongzhang, -- 1823-1901.; Longfellow, Charles Appleton -- Correspondence; Lowell, James Russell, -- 1819-1891 -- Correspondence; McCook, Anson G. -- 1835-1917 -- Correspondence; McKinley, William, -- 1843-1901 -- Correspondence; Mills, Stephen Crosby, -- Mrs. -- Correspondence; Morgan, Edwin D. -- 1811-1883 -- Correspondence; Phillips, Wendell, -- 1811-1884 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Schurz, Carl, -- 1829-1906 -- Correspondence; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Sickles, Daniel Edgar, -- 1819-1914 -- Correspondence; Smith, Hoke, -- 1855-1931 -- Correspondence; Stanley, Henry M. -- 1841-1904 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Taylor, Bayard, -- 1825-1878 -- Correspondence; Watterson, Henry, -- 1840-1921 -- Correspondence; White, Andrew Dickson, -- 1832-1918 -- Correspondence; Young, Dorothy Mills -- Correspondence; Young, G. R. -- 1891- -- Correspondence; Dow family; Library of Congress -- Officials and employees; United States Military Academy -- Students; Journalism -- United States; Voyages around the world -- History -- 19th century; United States -- Politics and government -- 19th century; Diplomats; Editors; Journalists; Librarians of Congress